Carotid Plaque Composition and the Importance of Non-Invasive in Imaging Stroke Prevention - Geiger, Martin Andreas (2022)
Luminal stenosis has been the standard feature for the current management strategies in patients with atherosclerotic carotid disease. Histological and imaging studies show considerable differences between plaques with identical degrees of stenosis. They indicate that specific plaque characteristics like Intraplaque hemorrhage, Lipid Rich Necrotic Core, Plaque Inflammation, Thickness and Ulceration are responsible for the increased risk of ischemic events. Intraplaque hemorrhage is defined by the accumulation of blood components within the plaque, Lipid Rich Necrotic Core is composed of macrophages loaded with lipid, Plaque Inflammation is defined as the process of atherosclerosis itself and Plaque thickness and Ulceration are defined as morphological features. Advances in imaging methods like Magnetic Resonance Imaging, Ultrasound, Computed Tomography and Positron Emission Tomography have enabled a more detailed characterization of the plaque, and its vulnerability is linked to these characteristics, changing the management of these patients based only on the degree of plaque stenosis. Studies like Rotterdam, ARIC, PARISK, CAPIAS and BIOVASC were essential to evaluate and prove the relevance of these characteristics with cerebrovascular symptoms. A better approach for the prevention of stroke is needed. This review summarizes the more frequent carotid plaque features and the available validation from recent studies with the latest evidence.